Enriching the Law School Curriculum: The Rise of Transactional Legal Clinics in U.S. Law Schools - Susan R. Jones; Jacqueline Lainez (Washington University Journal of Law & Policy, 2014)
More than fifteen years ago, the Clinical Law Review published "Small Business and Community Economic Development: Transactional Lawyering for Social Change and Economic Justice." In that article, Professor Susan R. Jones illustrated how shifting societal and political norms calling for increased individual economic self-reliance and the reduction of government entitlements resulted in the meaningful expansion of small business and community economic development legal clinics. The article presented a historical snapshot of the 1990s‘ age of welfare reform, and demonstrated how transactional legal clinics with a social and economic justice mission helped to promote community economic development. Since the publication of that article in 1997, transactional legal clinics have grown exponentially and have manifested in increasingly diverse transactional specialties, underscoring Professor Jones‘ argument that law school clinical programs must adapt to societal demands, as well as economic constraints and opportunities. This Article is a sequel to Professor Jones‘ 1997 article, one of the first scholarly articles to discuss transactional law clinics. It discusses developments in transactional clinical law teaching and practice over the last two decades, and the ways in which transactional clinics enrich legal education. Our thesis is this: Like their litigation counterparts, transactional clinics have evolved from a societal need, namely, the need to improve the economic conditions of low-income communities through business development.
Keywords: clinical legal education; legal education; legal education reform; u.s. law schools; law school curriculum